From the dual-dimensional perspective of employee mindfulness and superior trust, explore the influence mechanism of negative workplace gossip on work engagement - Cheng, Xiaoli; Duan, Jiaxin; Wu, Weilin; Lu, Lei (Frontiers in Psychiatry, 2023)
As a common phenomenon of workplace negative gossip in organizations, how it affects employees' work engagement is not yet clear, nor what methods can be used to mitigate its negative impact on employees' work engagement. Methods: Based on Conservation of Resource Theory, this study obtained 334 valid employee samples from mainland China enterprises through a three-time lagged research design and explored the mechanism of negative workplace gossip on work engagement from the dual perspectives of employees and supervisors. Results: The results show that: (1) Negative workplace gossip negatively affects employee work engagement. (2) Professional commitment plays a mediating role between negative workplace gossip and employee work engagement. (3) Employee mindfulness negatively moderates the negative impact of workplace negative gossip on professional commitment; superior trust negatively moderates the negative impact of workplace negative gossip on professional commitment. (4) Employee mindfulness and superior trust are further weakened to moderate the negative indirect impact of workplace negative gossip on employee work engagement through professional commitment, and this negative indirect impact is weaker when employees have a higher degree of mindfulness and higher trust in superiors. Discussion: It proposes effective strategies for managing workplace gossip to harness its positive influence and offer practical guidance to enhance employee work engagement.